DIALOG ESOTERIS: STUDI WACANA AL-QUR’AN SURAH AL-IKHLAS AYAT 1 - Chaer, Hasanuddin; Sirulhaq, Ahmad; Rasyad, Abdul (Jurnal Bahasa Lingua Scientia, 2020)
The purpose of this Qur'anic Discourse Study is to analyze the verses of the surah Al-Ikhlas verse 1 to find the essence of God's esoteric dialogue to the Prophet Muhammad. This discourse study uses interpretation of Al-Mukhtasor fi Tafsir Al-Qur?anil Kariim. At-tashniif: Jama?atin min Ulama?it tafsir and translation of the Qur'an. This research uses the method of social constructionist discourse study approach, namely how the relationship between knowledge and social processes in understanding discourse studies are managed through social processes.